Goalball as a Factor of Physical Rehabilitation of Students with Visual Impairments; Palaestra; Vol. 35, No. 3 - Kokhan S. T. Sergey Tikhonovich; Romanova E. V. Elena Veniaminovna; Nadeina L. V. Louise Vasilievna; Skaliy T. Tetiana; Kowalski V. Vitold; Petrova-Gotova Ts. Tsvetelina; Lazarova M. K. Mariya Krasimirova (2021, 2021)
Title screen